How Future Orientation is Associated with Depressive Symptoms in Multiethnoracial Adults: Basic Psychological Needs as a Mediator. Issue 1 (2nd January 2019) - Chang, Edward C.; Chang, Olivia D.; Yu, Elizabeth A.; Wu, Kaidi; Lucas, Abigael G.; Lui, P. Priscilla; Rollock, David; Chen, Xinjie; Hirsch, Jameson K.; Jeglic, Elizabeth L.
Abstract: We examined the role of basic psychological needs as a mediator of the association between future orientation and depressive symptoms in a sample of 202 (159 female and 43 male) multiethnoracial adults. Multiple mediation analysis with 10, 000 bootstraps was conducted to test for mediation. The association between future orientation and depressive symptoms was found to be accounted for by dimensions of basic psychological needs. Specifically, future orientation was negatively related to depressive symptoms through positive associations involving autonomy and competence, but not relatedness. The present findings are the first to not only point to the importance of examining future orientation in understanding depressive symptoms in multiethnoracial adults, but they are also the first to suggest possible mechanisms by which believing in a changeable future might foster stronger satisfaction of basic psychological needs, especially autonomy and competence, that might help multiethnoracials garner greater protection when encountering stressful situations in their lives.